Evaluation of phosphorus runoff from sandy soils under conservation tillage with surface broadcasted recovered phosphates. (15th February 2023) - Sohoulande, Clement D.D.; Szogi, Ariel A.; Stone, Kenneth C.; Sigua, Gilbert C.; Martin, Jerry H.; Shumaker, Paul D.; Bauer, Phil J.
Abstract: Potential new sources of phosphorus (P) fertilizer are the recovered P from livestock wastewater through chemical precipitation and the ash from combusting animal manures. Although most of the research on P losses from conservation tillage include high water-soluble P compounds from commercial fertilizer sources, information on the use of non-conventional, low water-soluble, recycled P sources is scarce. Particularly for sandy soils of the United States (US) Southeastern Coastal Plain region, research driven information on P loss into the environment is needed to determine recommendations for a direct use of new recycled P sources as crop P fertilizers. The objective of this study is to investigate the potential P runoff from sandy soils under conservation tillage, fertilized with recovered P from liquid swine manure and turkey litter ash in comparison with commercial P fertilizer triple superphosphate (TSP). The field study included two typical sandy soils of the US Southeastern Coastal Plain region, the Noboco and Norfolk. Simulated rain corresponding to the annual 30-min rainfall in the study site (Florence County, South Carolina) was applied to plots treated with recovered P from liquid swine manure, turkey litter ash, and TSP, including a control with no P added. The runoff was monitored and sampled every 5 min during the test and composite soil samples were collected from the top (0–15 cm) and subsurface (15–30 cm) soil layers in each plot. Laboratory analyses were conducted to quantify both total P (TP) and soluble reactive P (SRP) in runoff samples, and the soil test P in the soil layers. Two-way analyses of variances show significant treatment effects on both TP and SRP runoff. The quantities of SRP runoff from plots treated with the recovered P from swine manure and turkey litter ash represent respectively 1% and 7–8% of SRP runoff from plots treated with TSP. Hence, the use of the recovered P materials as crop P fertilizers through surface broadcast application present less environmental risks compared to commercial TSP. Highlights: Phosphorus (P) runoff evaluated for two recycled P materials from animal manure, commercial P, and a control on sandy soils. Plot-scale analyses show significant treatment effects, less P losses for recycled P materials. Broadcast application of recycled P materials presents less environmental risks. Recycled P materials could be an alternative to enhance soil nutrient management on sandy soils.